2011
DOI: 10.1111/j.1440-1800.2011.00520.x
|View full text |Cite
|
Sign up to set email alerts
|

The Kangaroo Program at a Brazilian maternity hospital: the preterm/low-weight babies’ health-care under examination

Abstract: The Kangaroo Program, originally developed in Colombia, was adopted as a public policy by the Brazilian Unified Health System (SUS) in 2000, in an effort to improve maternal and infant health in the country. This article aims to examine the Kangaroo Program as it is practiced and carried out at a maternity hospital in the northeastern Brazilian region. Through an institutional ethnographic approach, research demonstrates that the Kangaroo Program has been effective in saving lives and improving some of the inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 12 publications
0
12
0
1
Order By: Relevance
“…[43][44][45] Different studies have established the safety of KMC in intubated neonates under 1500 g and in extremely preterm infants. [46][47][48] Advantages for the mother All mothers can provide KMC, irrespective of age, parity, education, culture and religion. 49 Studies have demonstrated the impact of KMC on the mother-infant relationship, as well as on the mother's psychological well-being.…”
Section: Kangaroo Mother Care: Inception and Componentsmentioning
confidence: 99%
“…[43][44][45] Different studies have established the safety of KMC in intubated neonates under 1500 g and in extremely preterm infants. [46][47][48] Advantages for the mother All mothers can provide KMC, irrespective of age, parity, education, culture and religion. 49 Studies have demonstrated the impact of KMC on the mother-infant relationship, as well as on the mother's psychological well-being.…”
Section: Kangaroo Mother Care: Inception and Componentsmentioning
confidence: 99%
“…However, a study assessing 176 Brazilian maternity-hospitals, qualified between 2000 and 2003, shows that only 47.3% implemented the three stages of the method ( 11 ) . Véras and Traverso-Yépez ( 12 ) state that the implementation policy of the KM does not value the social, cultural, and environmental aspects involved in motherhood. Other authors suggest that the success of the implantation of the KM depends on the training of health professionals and the facilities the hospital offers to mothers for its permanence.…”
Section: Introductionmentioning
confidence: 99%
“…1 Thus, it tends to be compulsory in maternity wards linked to the SUS, and optional in the private health system. 4 The association between the MC implementation and public hospitals reinforces this statement. In addition, this fact may indicate that public services are more concerned with the incorporation of humanization in the care practice.…”
Section: Discussionmentioning
confidence: 87%
“…The MC in Brazil serves more families with low income and education levels than otherwise. 4 This can be explained by the fact that the MC is implemented in greater numbers in public services, where the majority of users have more vulnerable socioeconomic status. However, the social conditions of the city where the maternity is This suggests the failure in the ministerial statement -of being a maternity for risky births -on the part of state health departments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation